Study of the contribution of the 7Be(d, p) reaction to the 7Li problem in the Big-Bang Nucleosynthesis. (December 2020) - Inoue, Azusa; Tamii, Atsushi; Chan, Phaikying; Hayakawa, Seiya; Kobayashi, Nobuyuki; Maeda, Yukie; Nonaka, Kotaro; Shima, Tatsushi; Shimizu, Hideki; Tran, Dinh Trong; Wang, Xuan; Yamaguchi, Hidetoshi; et al.
Abstract: Our research goal is to measure the cross section of the 7 Be( d, p ) reaction to find a solution for the cosmological the 7 Li problem, which is an overestimation of the primordial 7 Li abundance in the standard Big-Bang nucleosynthesis (BBN) model. We developed a method to produce an unstable 7 Be target to measure the reaction in normal kinematics in a high-resolution measurement. We performed an experiment to produce the 7 Be target and also to measure the cross section of the 7 Be( d, p ) 8 Be reaction with the produced 7 Be target at the tandem facility, Kobe University. A 2.36 MeV proton beam irradiated a Li target to transmute 7 Li particles to 7 Be particles via the 7 Li( p, n ) 7 Be reaction. We produced 2.6×10 13 7 Be particles in the target after two days' proton irradiation. After the target production, the beam ion was changed to deuterons with energies of 0.6, 1.0, and 1.6 MeV to measure the 7 Be( d, p ) reaction. The outgoing protons were measured by two ΔE-E silicon telescopes placed at 30° and 45°. We report the preliminary results of this experiment, including the 7 Be( d, p ) cross section.